Web-based Computerized Land Activities Analysis - Boby Febriansah; Leon A. Abdillah (Universitas Bina Darma, 2020)
Information technology (IT) development in internet and web technologies have grown a variety of web-based services. Public services no longer require face-to-face activity, but can already be done virtually through web media. This research will evaluate land services at the ATR/BPN office in Ogan Ilir South Sumatra. The evaluation method used is the PIECES framework which consists of performance, information, economy, control, efficiency, and service. The questionnaire consists of 23 items and distributed using Google Forms. After analyzing the results of the questionnaire, five (5) variables are included in the